Pengembangan Composite Sandwich Carbon Fiber Cork Core Menggunakan Metode Vacuum Infusion Terhadap Kekuatan Bending - Muhammad Muhibuddin; Firman Yasa Utama (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Sandwich composites featuring carbon fiber skins and a cork core are lightweight materials with the potential to replace metals due to their high mechanical strength and eco-friendliness. This study aims to analyze the effect of varying the number of carbon fiber skin layers on the bending strength and failure modes of the sandwich composite. Specimens were fabricated using the vacuum infusion method with skin configurations of 4, 6, and 8 layers and tested via the three-point bending method in accordance with ASTM C393 standards. The results indicate that increasing the number of skin layers enhances the maximum bending load and core shear stress. The 8-layer configuration yielded the highest maximum bending load (66.47 kg) and core shear stress (0.769 MPa), whereas the highest face bending stress (294.62 MPa) was observed in the 4-layer configuration. Face yielding was the dominant failure mode across all specimens. The findings demonstrate that the number of skin layers influences the bending strength characteristics of carbon fiber/cork core sandwich composites.